5 main areas of work of a PR specialist in health care organizations - Moldabayev Х.С. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2018)
The country is implementing reforms in the health sector. One of the recently adopted large-scale governmental programs is Digital Kazakhstan. The document covers many areas of activity, including the health sector. The program focuses on the work on digitalization of state bodies. The goal of the program is to improve the quality of medical services, making them accessible to all citizens of the country. However, all these innovations do not reach the common people, especially in villagers and remote auls, who do not even know what digitalization is. In this regard, the important role is played by the work of the department of public relations or a specialist in PR. The article considers the measures taken by the public relations specialist. Particular attention is paid to 5 main areas that should be implemented by a specialists in the work.